2014
DOI: 10.1536/ihj.14-150
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Mediated Drug Delivery System for Cardiovascular Disease

Abstract: SummaryAdministration of drugs and other therapeutic agents has been the central strategy of contemporary medicine for cardiovascular disease. The use of a drug delivery system (DDS) is always demanded to enhance the efficacy and safety of therapeutic agents, and improve the signal-to-noise ratio of imaging agents. Nano-scale materials modify in vivo drug kinetics, depending on (patho)physiological mechanisms such as vascular permeability and incorporation by the mononuclear phagocyte system, which constitute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 54 publications
0
50
0
2
Order By: Relevance
“…[14][15][16][17] We recently reported that nanoparticle-mediated delivery of pitavastatin showed significant therapeutic effects on pulmonary arterial hypertension, 18) restenosis, 19) ischemia-reperfusion injury, 20) and atherosclerosis 21) in animals by inhibiting the MCP1-CCR2 pathway. Because PLGA nanoparticles are delivered selectively to inflammatory cells (mainly monocytes) after intravenous administration, 21,22) it is suggested that monocyte-mediated inflammation plays an important role in the mechanism by which pitavastatin-NP exerted beneficial effects in these previous studies.…”
Section: Editorial P472mentioning
confidence: 99%
“…[14][15][16][17] We recently reported that nanoparticle-mediated delivery of pitavastatin showed significant therapeutic effects on pulmonary arterial hypertension, 18) restenosis, 19) ischemia-reperfusion injury, 20) and atherosclerosis 21) in animals by inhibiting the MCP1-CCR2 pathway. Because PLGA nanoparticles are delivered selectively to inflammatory cells (mainly monocytes) after intravenous administration, 21,22) it is suggested that monocyte-mediated inflammation plays an important role in the mechanism by which pitavastatin-NP exerted beneficial effects in these previous studies.…”
Section: Editorial P472mentioning
confidence: 99%
“…(20)(21)(22) NPs are taken up by the target organ because of their small size and permeability and their retention effect. Drug release from NPs is controlled according to the NP composition.…”
Section: Nanoparticle-mediated Drug Delivery System (Nano-dds)mentioning
confidence: 99%
“…Two polymers, poly(lactide) (PLA) and poly(lactide-co-glycolide) (PLGA), are used for the synthesis of FDA-approved polymeric biodegradable nano-DDS. (21,23) This type of nanoparticle can be used to achieve the sustained release of encapsulated drug, which takes place concomitantly with the degradation of PLA or PLGA. Various chemicals and nucleotides are incorporated in liposomes and polymers.…”
Section: Nanoparticle-mediated Drug Delivery System (Nano-dds)mentioning
confidence: 99%
“…Nanoparticles (NPs) have been used as a novel delivery system for the transport of drugs to target organs [19,20,21]. NPs are taken up by the target organ because of their small size, permeability, and retention effect.…”
Section: Nano-ddsmentioning
confidence: 99%